2011
DOI: 10.1029/2010jb007724
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic seismic ruptures on melting fault zones

Abstract: [1] We present a physical model that describes the behavior of spontaneous earthquake ruptures dynamically propagating on a fault zone and that accounts for the presence of frictional melt produced by the sliding surfaces. First, we analytically derive the solution for the temperature evolution inside the melt layer, which generalizes previous approximations. Then we incorporate such a solution into a numerical code for the solution of the elastodynamic problem. When a melt layer is formed, the linear slip-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 48 publications
(124 reference statements)
3
38
0
Order By: Relevance
“…We emphasize here that in the present model the final level of stress is not prescribed, as in the case of the linear slipweakening friction law, but it is itself a part of the solution. The same occurs for other governing models, such as the flash heating of asperity contacts and melting of rock and gouge, which also exhibit a dramatic fault weakening [Andrews, 2002;Bizzarri and Cocco, 2006;Bizzarri, 2009;Rice, 2006;Bizzarri, 2011a]. Indeed, Bizzarri and Spudich [2008] have shown that the inclusion of the thermal pressurization of the pore fluids can cause a supershear regime in a configuration which would produce a subshear propagation when the fluid migration is ignored (so that a linear slipweakening governs the fault), regardless the value of the initial shear stress.…”
Section: Dramatic Fault Weakening and Low Frictionmentioning
confidence: 96%
See 3 more Smart Citations
“…We emphasize here that in the present model the final level of stress is not prescribed, as in the case of the linear slipweakening friction law, but it is itself a part of the solution. The same occurs for other governing models, such as the flash heating of asperity contacts and melting of rock and gouge, which also exhibit a dramatic fault weakening [Andrews, 2002;Bizzarri and Cocco, 2006;Bizzarri, 2009;Rice, 2006;Bizzarri, 2011a]. Indeed, Bizzarri and Spudich [2008] have shown that the inclusion of the thermal pressurization of the pore fluids can cause a supershear regime in a configuration which would produce a subshear propagation when the fluid migration is ignored (so that a linear slipweakening governs the fault), regardless the value of the initial shear stress.…”
Section: Dramatic Fault Weakening and Low Frictionmentioning
confidence: 96%
“…The comparison between the present model and the viscous behavior of a continuous layer of an high viscosity molten material [Bizzarri, 2011a] is discussed in Appendix B.…”
Section: Physical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, both thermal pressurization of pore fluids and flash heating predict not only a very dramatic stress drop, but also a very high peak in fault slip velocity, so that the final result is that melting temperature is very often exceeded, unless the slipping zone is extremely large [Bizzarri and Cocco, 2006b;Bizzarri, 2009]. Bizzarri [2011a] stressed that when melting occurs, the rheological behavior of the fault zone no longer obeys the Coulomb-AmontonMohr formulation, in that a viscous rheology is needed to describe the traction evolution during the ruptures.…”
Section: Introductionmentioning
confidence: 99%